Morphogeometric Evaluation of the Left Ventricle and Left Atrioventricular Ring in Dogs: A Computerized Anatomical Study - Cardoso, Catarina Borges [UNESP]; Brandão, Cláudia Valéria Seullner [UNESP]; Juliani, Paulo Sérgio; Filadelpho, André Luis [UNESP]; Pereira, Geovane José [UNESP]; Lourenço, Maria Lúcia Gomes [UNESP]; Hataka, Alessandre [UNESP]; Padovani, Carlos Roberto [UNESP] (MDPI, 2023)
In veterinary, there is scarce availability of morphogeometric studies in normal and remodeled hearts; furthermore, ventricular geometry acts as an indicator of cardiac function. It is a highly necessary field of knowledge for the development of therapeutic protocols, especially surgical ones. The objectives of this study were: to obtain measurements of the left atrioventricular valve ring and left ventricle, to analyze the proportionality between the segments of the left cardiac chamber of normal hearts and to describe reference values for morphogeometric analysis of the left ventricle. For this, 50 hearts from small (Group 1—G1) and medium to large (Group 2—G2) dogs were laminated in the apical, basal and equatorial segments, and submitted to computer analysis to identify the perimeter of each segment and the left atrioventricular ring, wall thickness and distance from the atrioventricular sulcus to the apex. The largest internal perimeter was that of the equatorial. The basal segment had the highest mean for ventral parietal wall thickness, suggesting greater contractile reserve at that location. Considering the proportionality relationships, there was no statistical difference between the intersegmental perimeter indices for the two groups. This suggests that despite the animals’ weight variations, the proportions between the left ventricular segments are maintained. Therefore, it is concluded that the data can be used as a standard of comparison for cardiac geometric assessments, as well as a basis for the development of therapeutic measures in the context of adverse cardiac remodeling.
Keywords: anatomy; cardiac remodeling; cardiac surgery; myocardium; ventricular geometry